1964
DOI: 10.1093/ajcn/14.6.342
|View full text |Cite
|
Sign up to set email alerts
|

The Requirement of Magnesium by the Normal Adult

Abstract: I T IS hoped that Perspectives in Nutrition will review the literature selectively, interpret it moderately and present a spectrum of ideas that will serve as a continual stimulation to nutritional research applied to medical problems. M AGNESIUM has been accepted as an essential nutrient for the rat since 1932 when Kruse, Orent and McCollum 1 induced an acute magnesium deficiency syndrome in rats. The characteristics of magnesium deficiency were then studied in rats and in other laboratory animals by these in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(63 citation statements)
references
References 107 publications
3
60
0
Order By: Relevance
“…One might, therefore, expect to find less of the ingested magnesium appearing in the feces in our hypothyroid than our hyperthyroid patients-an expectation just opposite to our findings. Furthermore, a comparison of our data to composite balance data and graphs of Seelig (27) indicates that our results cannot be explained on the basis of intake alone. The magnitude of negative balance in our hypothyroid patients during therapy exceeds any recorded for normal subjects on similar intakes of magnesium and calcium, and our hyperthyroid patients had strikingly positive balances in contrast to those reported in normal subjects on similar magnesium and calcium intakes.…”
Section: Methodsmentioning
confidence: 65%
See 1 more Smart Citation
“…One might, therefore, expect to find less of the ingested magnesium appearing in the feces in our hypothyroid than our hyperthyroid patients-an expectation just opposite to our findings. Furthermore, a comparison of our data to composite balance data and graphs of Seelig (27) indicates that our results cannot be explained on the basis of intake alone. The magnitude of negative balance in our hypothyroid patients during therapy exceeds any recorded for normal subjects on similar intakes of magnesium and calcium, and our hyperthyroid patients had strikingly positive balances in contrast to those reported in normal subjects on similar magnesium and calcium intakes.…”
Section: Methodsmentioning
confidence: 65%
“…Seelig (27) in an exhaustive review of previously published magnesium balance data, concluded that the reported magnesium requirement of 18 to 25 mEq per day (220 to 300 mg) is low and that with intakes below 0.5 mEq per kg per day (6 mg per kg), negative magnesium balance is likely to develop, particularly in men. High intakes of protein, calcium, vitamin D, or alcohol were found to impede retention or to increase the requirement of magnesium, especially in those on low magnesium intakes.…”
Section: Methodsmentioning
confidence: 99%
“…As to the intestinal effect of parathyrin and vitamin D, it should be mentioned that contradictory results, i.e. an increase in magnesium absorption, have been reported by other authors (118)(119)(120).…”
Section: Parathyrinmentioning
confidence: 94%
“…Evidence suggests that the occidental "American diet" is relatively deficient in magnesium, whereas the "Oriental diet," which is characterized by a greater intake of fruits and vegetables, is rich in magnesium. 31 It has also been observed that CAD patients absorb more magnesium during magnesium loading testing than do those without CAD, suggesting that CAD is associated with excessive magnesium loss and a relative magnesium-deficient state. 32 Evidence suggests that endothelial dysfunction may be the initiating event in the atherosclerotic process that subsequently leads to clinical CAD.…”
Section: Shechter Et Al Magnesium Improves Endothelial Functionmentioning
confidence: 99%